INTERSEX IN A DOG PRESENTING VULVA, HEMIPENIS AND PENILE BONE - Suede de Sousa Moura, Laila; Monteiro Filho, Flávio; Carolina Rodrigues Cunha, Ana; Thainar Mendes Cunha, Andrielle (Journal of Interdisciplinary Debates, 2023)
Intersex is an anomaly in the reproductive system, which characterizes animals that have ambiguity in the genital system. The documented report is of a dog that presented abnormalities in the external genitalia, with the presence of a hemipenis in its vulva. The animal was submitted to hormone dosage of progesterone, testosterone and estrogen. Imaging tests such as ultrasound and X-rays were performed, with an exploratory celiotomy and histopathology being chosen as the therapeutic approach. According to the findings in the imaging exams, testicular structure was observed in the location of the ovaries, and in the x-ray images it was possible to observe the presence of underdeveloped penile bone in the hemipenis. Hormone dosage indicated significant changes in testosterone increase 2,300 pg/ml, estrogen concentrations were 8.00 pg/ml being normal and high progesterone 0.91 ng/ml. Microscopic findings in histopathology indicated testicular structure present in the ovaries, thus concluding the diagnosis of true hermaphroditism.